Unintended medication discrepancies and associated factors upon patient admission to the internal medicine wards: identified through medication reconciliation - Tilaye Arega Moges; Temesgen Yihunie Akalu; Faisel Dula Sema (BMC Health Services Research, 2022)
Abstract Background Medication reconciliation (MedRec) is a widely accepted tool for the identification and resolution of unintended medication discrepancies (UMD). Objective This study aimed at assessing the magnitude and associated factors of UMD identified through medication reconciliation upon patient admission to the internal medicine wards. Methods Prospective cross-sectional study was conducted at the internal medicine wards of Felege Hiwot and Tibebe Ghion comprehensive specialized hospitals in Bahir Dar city, Northwest Ethiopia, from May 01 to July 30, 2021. Data were collected by using a data abstraction format prepared based on standard MedRec tools and previous studies on medication discrepancy. Pharmacists-led MedRec was made by following the WHO High5s “retroactive medication reconciliation model”. SPSS® (IBM Corporation) version 25.0 was used to analyze the data with descriptive and inferential statistics. A binary logistic regression analysis was used to identify factors associated with UMD. A statistical significance was declared at a p-value < 0.05. Results Among 635 adult patients, 248 (39.1%) of them had at least one UMD. The most frequent types of UMDs were omission (41.75%) and wrong dose (21.9%). The majority (75.3%) of pharmacists’ interventions were accepted. Polypharmacy at admission (p-value < 0.001), age ≥ 65 (p-value = 0.001), a unit increase on the number of comorbidities (p-value = 0.008) and information sources used for MedRec (p-value < 0.001), and medium (p-value = 0.019) and low adherence (p-value < 0.001) were significantly associated with UMD. Conclusion The magnitude of UMD upon patient admission to the internal medicine wards was considerably high. Omission and the wrong dose of medication were common. Older age, polypharmacy, low and medium adherence, and an increase in the number of comorbidities and information sources used for MedRec are significantly associated with UMDs. Pharmacists' interventions were mostly acceptable. Thus, the implementation of pharmacists-led MedRec in the two hospitals is indispensable for patient safety.